A WIDE-BASE POPULATION PYRAMID AND OTHER FACTORS EXPLAIN LOW MORTALITY IN PAKISTAN DURING COVID-19 PANDEMIC - Khan, Farhan; Siddiqui, Humayun (Journal of Ayub Medical College Abbottabad, 2022)
World is experiencing an unprecedented pandemic of COVID-19 for over a year. This viral infection outbreak originated in December 2019 at Wuhan, China and within three months became a global pandemic. The outbreak has affected over 200 countries and territories of the world. Despite of having well-established health care system, countries such as China, Italy, Iran, Spain, France, Germany and USA have experienced a high death toll in this pandemic. Pakistan although being geographic neighbor of China and Iran, is somehow protected from the otherwise expected high case-fatality of COVID-19. This papers explains what factors have protected Pakistan from a high mortality in this pandemic.